Fauna de Coleoptera Lamellicornia de la región de Tépic, Nayarit, México. - Morón, Miguel Ángel; Deloya, Cuauhtémoc; Ramírez Campos, Agustín; Hernández Rodríguez, Salvador (Instituto de Ecología, A.C., 1998)
A comparative analysis of the scarab beetle fauna of the area of Tepic, Compostela and San José Mojarras, Nayarit, México is presented. Data were obtained during 1994-1996 with 239 days of collecting effort in sugar cane fields with remnants of tropical deciduous forost and oak forest, between 850 1200 m altitude. Records of 11 subfamilies, 22 tribes, 52 genera and 122 species are included. Specific diversity consisied of Melolonthinae (36 spp.), Dynastinae (20 spp,), Scarabaeinae (1 / spp.), Aphodiinae (17 spp.) and Rutelinac (14 spp.). About 50% of the specific diversity is concentrated in the genera Phyllophaga (23 spp.), Diplotaxis (11 spp.), Anómala (9 spp.), Cyclocephala (9 spp.) and ataenius (10 spp.). Phyllophaga dentex, Ph. ravida, Ph. lenis, Ph. lalanza. Ph. brevidens, Ph. obsoleta. Id), fulviventris Ph. pruinosa, DipIotaxis superflua. Anómala subaenea, Cyclocephala freudei and C. lunulata were tht; rnost abundant species in the samples. The scarab beetle fauna of Tepic area shows 35% similarity with the area of Chamela Jalisco, and 33% similarity witli the southern part of Mtirelos state and represent 8.3% of the lamellicornian species rocorded in México.